PENGARUH PENGETAHUAN TEKNOLOGI, MOTIVASI KERJA, DAN SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU - Yuliani, Gita Rahma; Niati, Asih; Rizkiana, Citra (Universitas Bina Taruna Gorontalo, 2025)
This study aims to find out the factors that influence teacher performance, namely the influence of technology,work motivation and implementation of supervision by school principals in improving teacher performance at the Husnul Khatimah Foundation. The method used in this research is quantitative research with data collection techniques through questionnaires with a sample of 48 respondents and using purposive sampling. The results of the analysis show that the variable knowledge of technology has no positive and significant effect on teacher performance. High or low technological knowledge possessed by a teacher cannot affect the results of teacher performance at the Husnul Khatimah Foundation. The variables of work motivation and principal supervision have a positive and significant effect on teacher performance. In improving teacher performance, it is necessary to provide guidance by the principal in the form of coaching activities and training programs on a regular basis and build the motivation of each teacher. The coefficient of determination (Adj R²) is 0.777 which means that the teacher's performance variable can be influenced by the variables of technological knowledge, work motivation and school principal supervision by 77.7%, while the rest is influenced by other variables outside the model studied.